The Choice of Healthcare Providers for Febrile Children after Introducing Non-professional Health Workers in a Malaria Endemic Area in Papua New Guinea - Tsukahara, Takahiro; Ogura, Seiritsu; Sugahara, Takuma; Sekihara, Makoto; Furusawa, Takuro; Kondo, Naoki; Mita, Toshihiro; Endo, Hiroyoshi; Hombhanje, Francis (Frontiers in Public Health, 2015)
Background: Disease burden of malaria in Papua New Guinea (PNG) is the highest in Asia and the Pacific, and prompt access to effective drugs is the key strategy for controlling malaria. Despite the rapid economic growth, primary healthcare services have deteriorated in rural areas; the introduction of non-professional health workers [village health volunteers (VHVs)] is expected to improve antimalarial drug deliveries. Previous studies on PNG suggested that distance from households negatively affected the utilization of health services; however, price effect on healthcare demand decisions has not been explored. Empirical studies on household’s affordability as well as accessibility of healthcare services contribute to policy implications such as efficient introduction of out-of-pocket costs and effective allocation of health facilities. Therefore, we investigate price responsiveness and other determinants of healthcare provider choice for febrile children in a malaria endemic rural area wherein VHVs were introduced. Methods: Cross-sectional surveys were conducted using a structured questionnaire distributed in a health center’s catchment area of East Sepik Province in the 2011/2012 rainy seasons. Caretakers were interviewed and data on fever episodes of their children in the preceding two weeks were collected. Mixed logit model was employed to estimate the determinants of healthcare provider choice. Results: Among 257 fever episodes reported, the main choices of healthcare providers were limited to self-care, VHV, and a health center. Direct cost and walking distance negatively affected the choice of a VHV and the health center. An increase of VHV’s direct cost or walking distance did not much affect predicted probability of the health center, but rather that of self-care. While, drug availability and illness severity increased the choice probability of a VHV and the health center. Conclusion: The results suggest that the net healthcare demand increases with the introduction of a VHV. Allocations from the government’s budget are required to sustain VHV activities because the introduction of a small user fee could impede the utilization of a VHV. A large travel cost related to the choice of the health center suggests that resource allocation is required for the expansion of formal healthcare providers to adequately operate a referral system.